Human Intrinsic Factor Expression for Bioavailable Vitamin B12 Enrichment in Microalgae - Serena Lima; Conner L. Webb; Evelyne Deery; Colin Robinson; Julie A. Z. Zedler (Biology, 2018)
Dietary supplements and functional foods are becoming increasingly popular complements to regular diets. A recurring ingredient is the essential cofactor vitamin B12 (B12). Microalgae are making their way into the dietary supplement and functional food market but do not produce B12, and their B12 content is very variable. In this study, the suitability of using the human B12-binding protein intrinsic factor (IF) to enrich bioavailable B12 using microalgae was tested. The IF protein was successfully expressed from the nuclear genome of the model microalga Chlamydomonas reinhardtii and the addition of an N-terminal ARS2 signal peptide resulted in efficient IF secretion to the medium. Co-abundance of B12 and the secreted IF suggests the algal produced IF protein is functional and B12-binding. Utilizing IF expression could be an efficient tool to generate B12-enriched microalgae in a controlled manner that is suitable for vegetarians and, potentially, more bioavailable for humans.